2021
DOI: 10.3390/agronomy11102055
|View full text |Cite
|
Sign up to set email alerts
|

Potato Yield Response and Seasonal Nitrate Leaching as Influenced by Nitrogen Management

Abstract: Nitrate leaching is of great environmental concern, particularly with potatoes grown on sandy soils. This 3-year study evaluated the effect of three N rates (100, 150, and 200 kg ha−1) of single applications of polymer-coated urea (PCU) and a 75% PCU + 25% urea mixture, plus a conventional split application of 200 kg N ha−1 of a 50% ammonium sulfate + 50% calcium ammonium nitrate mixture (CONV) on NO3−-N leaching, potato yield, and N uptake under irrigated and non-irrigated conditions on a sandy soil in Quebec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
(77 reference statements)
1
8
0
Order By: Relevance
“…As expected, fields where the total water inputs exceeded seasonal ETo recorded the highest drainage. It is well documented that drainage in sandy soils increases with greater total water input [36,37]. The risk of drainage in sandy soils with a lower water holding capacity is high after a major rain event.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, fields where the total water inputs exceeded seasonal ETo recorded the highest drainage. It is well documented that drainage in sandy soils increases with greater total water input [36,37]. The risk of drainage in sandy soils with a lower water holding capacity is high after a major rain event.…”
Section: Discussionmentioning
confidence: 99%
“…Potato growers can easily shift to polymer coated urea (PCU) instead of the conventional split N application without significantly reducing tuber yield [110]. Under irrigated conditions, the use of PCU and PCU + urea at the same N rate applied at planting led to a significant rise in seasonal NO 3 − leaching by 32% and 43%, respectively, when compared to the conventional split N treatment [105]. Clement et al [105] concluded that the use of PCU alone is more environmentally sound and profitable than a PCU + urea mixture for potato production in sandy soils.…”
Section: Impacts Of N Fertilizer Application Methods On Yield and Yie...mentioning
confidence: 99%
“…Under irrigated conditions, the use of PCU and PCU + urea at the same N rate applied at planting led to a significant rise in seasonal NO 3 − leaching by 32% and 43%, respectively, when compared to the conventional split N treatment [105]. Clement et al [105] concluded that the use of PCU alone is more environmentally sound and profitable than a PCU + urea mixture for potato production in sandy soils. They also recorded a higher N uptake, dry matter content, and apparent N recovery under PCU + urea as compared to PCU alone and the conventional split N application method [105].…”
Section: Impacts Of N Fertilizer Application Methods On Yield and Yie...mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to excessive irrigation water and chemical fertilizer inputs, the irrigated potato production systems could be a potential source of nitrate contamination in underground water [15]. Nitrate leaching beyond crop root zone increased with increasing nitrogen fertilizer rates under irrigated conditions as compared to non-irrigated potatoes [16]. A study by Vashisht et al [17] predicted that the current potato production level could not be achieved even with the increased water and nitrogen input levels, while there could be 41-67% anticipated increase in leaching losses by the years 2058-2067.…”
Section: Introductionmentioning
confidence: 99%